Structural reform and productivity growth in emerging Europe and Central Asia - Yordan Georgiev; Piroska Nagy-Mohacsi; Alexander Plekhanov (Asian Development Bank (ADB), 2017)
Since 1990, countries in emerging Europe and Central Asia have undergone comprehensive economic transformation. These reforms helped achieve an impressive degree of income convergence toward the levels of the advanced economies, although at the cost of rising inequality and lower life satisfaction. Over the last decade, both the speed of reforms and economic growth have slowed down markedly. To sustain convergence, greater emphasis needs to be put on structural reforms, facilitating innovation and boosting firm productivity while, at the same time, taking into account the distributional impact of reforms.
Keywords: O57; P24; 330; economic growth; structural reform; transition